The Concept of "Austin and Jeremy Bentham" and Its Relevance to the Construction of Indigenous People - Salam, Safrin; Karim, La Ode Muhammad; Gurusi, La; Kaswandi, Kaswandi; Tonny, Fajrin; Dewi, Rasmala (Journal of Transcendental Law, 2024)
The concepts of positivism and utilitarian schools show differences in regulating or interpreting society and individual rights. The purpose of this research is to find the views of the pure law school and the utilitarian law school in reconstructing indigenous peoples. This research uses normative legal research. In its study, this research uses several approaches, namely the statutory approach and the concept approach. The results showed that John Austin's pure legal school places the construction of indigenous peoples in the standard norms contained in Article 18 B paragraph (2) of the 1945 Constitution. This flow limits the interpretation of the construction of indigenous peoples. Meanwhile, according to the utilitarian legal school of Jeremy Bentham, the view of Article 18 B paragraph (2) of the 1945 Constitution as the basis for the construction of indigenous peoples shifts by interpreting the existence of indigenous peoples is not only seen as law an sich, but the legal regulation of legal communities is seen in 3 (three) aspects, namely a) indigenous peoples are seen in the position of legal reality; b) Customary law becomes a translation of the legal provisions referred to in Article 18 B paragraph (2) of the 1945 Constitution; c) Recognition and protection of the law of indigenous peoples are constructed in the aspect of legal reality. Thus, the utilitarian school of law opens a new approach in the construction of indigenous peoples that is not only reviewed from the norms an sich in statutory regulations but the existence of utilitarian schools of law can be used to open more lively legal spaces in constructing recognition and protection of the rights of indigenous peoples as subjects of law.